DNA BARCODING OF ANEMONE OBTUSILOBA VAR. POTENTILOIDES: A THREATENED AND ENDEMIC PLANT FROM WESTERN HIMALAYAN REGION OF PAKISTAN - S. Umer; K. Muhammad; A. Majid; Aziz Ud-Din; H. Ahmad (Journal of Animal and Plant Sciences, 2022)
Endemic flora is the bio-assets of a country being medicinally important with economic potential. But unfortunately, these plants are endangered and may become extinct because of their limited geographic distribution and small population size. DNA barcoding is one mong the prime steps for conservation of a threatened species. Anemone obtusiloba var. potentilloides (Camb. ex Berant.) Lauener is an endemic plant species belonging to the family Ranunculaceae. The main aim of this study was to find the most effective DNA barcode regions for species identification and authentication. In this study, we used four DNA barcode markers (matK, rbcL,trnH-psbA and ITS) to explore their effectiveness and efficacy for correct identification of Anemone obtusiloba var. potentilloides. We examined their efficacy on the bases of amplification and sequencing success rate. The data was analysed by BLAST sequence similarity, TAXONDNA and the Neighbour Joining Tree Method. The universal DNA barcode markers namely rbcLtrnH-psbA and ITS had shown good amplification and sequence rate while matK remained challengeable. After evaluation of the candidate barcodes, only rbcL region had shown the highest number of variable sites (1142) as compared to other barcodes. Similarly, rbcL came up with the highest score of species identification with 98% and 80.55% in BLAST and TAXONDNA analyses respectively. In cladding analysis, the highest model support was in rbcL having the highest bootstrap value as 89% with its relative species. The finding of current study supports rbcL as the best DNA barcode for the identification of Anemone obtusiloba var. potentilloides. Moreover, other candidate barcodes were not found efficient for correct identification of the species. This work has useful applications in the field of biodiversity conservation.
Keywords: Endemic flora; rbcL; DNA barcode; Phylogenetic analysis; biodiversity conservation